2017
DOI: 10.1093/aobpla/plx031
|View full text |Cite
|
Sign up to set email alerts
|

Local shifts in floral biotic interactions in habitat edges and their effect on quantity and quality of plant offspring

Abstract: Habitat variations influence the richness and composition of insect guilds. This affects plant reproduction, which depends upon functional relationships with insects, responsible for both pollination and predation. Major consequences can occur in composite landscapes, where forest fragmentation produces transition habitats showing a great heterogeneity over short-spatial scales. We studied herbivory and pollination in an edge-specialist carnation over a forest-open habitat gradient. Visiting insects varied ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The high levels of herbivory observed in the natural population indicated that this could be an important threat for the species due to it also affects the traits to attract pollinators (Gargano et al, 2017). In the translocated population the herbivory was lower because of the fence, but did not eliminated it.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The high levels of herbivory observed in the natural population indicated that this could be an important threat for the species due to it also affects the traits to attract pollinators (Gargano et al, 2017). In the translocated population the herbivory was lower because of the fence, but did not eliminated it.…”
Section: Discussionmentioning
confidence: 98%
“…Godefroid et al, 2011;Cogoni et al, 2013;Fenu et al, 2019). However, the population's persistence depends on several factors as the species' longevity, mating system, dispersal ability (Picó and Van Groenendael, 2007), the presence of inbreeding depression, outbreeding depression (Weisenberger et al, 2014), pollen limitation , reproductive success (Schemske et al, 1994), interaction between pollinators and herbivory (Gargano et al, 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study by Gargano et al . (2017) on germination of seeds of the perennial herb Dianthus balbisii (Caryophyllaceae) produced via open-pollination vs hand-pollination over a forest-open habitat gradient at five levels of illuminance in southern Italy are briefly described in Appendix B. The authors indicate that illuminance along the ecotone gradient ranges from <500 klux to >4000 klux.…”
Section: Methodsmentioning
confidence: 99%
“…Although previous work has quantified seed production (e.g. Kunin 1997 ; Burgess et al 2006 ; Ison and Wagenius 2014 ; Gargano et al 2017 ) and mate diversity ( Barriball et al 2014 ) for edge versus interior plants, the effects of spatial position on siring success and the extent of pollen-mediated gene dispersal have not previously been explored.…”
Section: Introductionmentioning
confidence: 99%